Measurement of Lipid Supplements in Poultry Feed by Infrared Spectroscopy - Holser, Ronald A.; Hawkins, Samantha A. (International Journal of Poultry Science, 2011)
Rapid measurement of a fatty acid supplement in poultry feed formulations was performed using near Infrared (NIR) spectroscopy with chemometric analysis. A standard feed formulation was amended with up to 10 wt% fatty acid supplement containing Docosahexaenoic Acid (DHA) and scanned from 10,000 cm-1 to 4000 cm-1. Spectra were evaluated by Principal Component Analysis (PCA) to detect outliers followed by Partial Least Square (PLS) regression. Models were developed with first derivative spectra. A typical dataset of 36 spectra was subdivided with 30 spectra used for model calibration and 6 spectra for the validation set. The PLS model produced a regression coefficient of 0.98314 with an RMSEC value of 0.44772. This technique provided a rapid method to analyze the amount of fatty acids in supplemented feeds.